PERAN KOPERASI SIMPAN PINJAM TERHADAP PERKEMBANGAN PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN LEMBATA - Heribertus Gaspar Baru; Fransina W. Ballo; Maria Indriyani Hewe Tiwu (E-Jurnal Ekonomi Pembangunan, 2024)
This research aims to determine the role of the Ankara Kopdit savings and loan cooperative in developing micro, small and medium enterprises (MSMEs) in Lembata Regency and to determine the efforts made by the Ankara savings and loan cooperative in empowering business actors in Lembata Regency. This research uses a qualitative approach. Data collection techniques were carried out using observation, interviews and documentation. The number of informants in this research was 8 people consisting of 1 employee of Ksp Kopdit Ankara and 7 MSME actors. The results of this research are: 1.) The role of the Ankara Kopdit Savings and Loans Cooperative in the development of MSMEs in Lembata Regency is as a capital financing party in the activities of MSME players to increase members' income and as a savings institution other than banks. 2.) The efforts of the Kopdit Ankara savings and loan cooperative are to empower the community's economy through providing activity counseling and activity assistance to improve the performance of business actors to be able to survive competition in the world of work. Keywords: Role, Saving and Loan Cooperative, Micro Small Medium Enterprises (MSME)